2005
DOI: 10.1158/0008-5472.can-05-1098
|View full text |Cite
|
Sign up to set email alerts
|

High Frequencies of Functional Tumor-Reactive T Cells in Bone Marrow and Blood of Pancreatic Cancer Patients

Abstract: Pancreatic cancer is characterized by aggressive growth and treatment resistance. New approaches include immunotherapeutic strategies but the type and extent of spontaneous immune responses against tumor antigens remains unclear. A dominance of TH2 cytokines in patients' sera reported previously suggests systemic tumor-induced immunosuppression, potentially inhibiting the induction of tumor-reactive T cells. We characterized the localization, frequencies, and functional potential of spontaneously induced memor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
111
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 25 publications
10
111
0
1
Order By: Relevance
“…Th1 cells play an important role in anti-tumor immune responses by producing a panel of cytokines such as IFNγ and TNFα [1,2]. IL-12 enhances Th1 cell polarization, leading to more IFNγ and TNFα production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Th1 cells play an important role in anti-tumor immune responses by producing a panel of cytokines such as IFNγ and TNFα [1,2]. IL-12 enhances Th1 cell polarization, leading to more IFNγ and TNFα production.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that CD4+ T cells (also called Th1 cells) play an important role in anti-tumor immune responses [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor size was measured three times weekly and determined by the product of perpendicular diameters. Mice were euthanized when the tumor size exceeded 200 mm 2 or with the appearance of distress.…”
Section: Tumor Inductionmentioning
confidence: 99%
“…2,2125 This polyvalent T cell pool consists of effector and central T mem cells, which produce IFN-γ upon Ag re-encounter and can eliminate autologous tumor cells. 2628 However, there is increasing evidence that tumor-associated immune suppression can be mediated in an Ag-specific manner, too. Our group has previously shown that TA-specific T reg cells are present in cancer patients, which can suppress the proliferation of polyclonally activated conventional T cells (T con cells) and inhibit TA-specific effector T cell responses in vitro .…”
Section: Introductionmentioning
confidence: 99%